2017
DOI: 10.1111/ctr.13136
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of lactate clearance for the development of early allograft dysfunction and short‐term prognosis in deceased donor liver transplantation

Abstract: This retrospective study evaluated lactate clearance (LC), measured at 6, 12, 18, and 24 hours after reperfusion, as a predictor of early allograft dysfunction (EAD) and short-term outcomes in patients receiving deceased donor liver transplantation. Of 181 transplant recipients, 44 (24.3%) developed EAD and had lower LCs than those who did not develop EAD. A receiver operating characteristic analysis showed that LC determined at 6 hours showed the highest area under curve value of 0.828 (95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…An incremental increase in arterial lactate reflects the failure of the Cori cycle, another signal of mitochondrial dysfunction [27-29]. In recent reports, arterial lactate was a predictor of graft dysfunction in liver transplantation, although further studies are needed to determine the best time point for lactate measurement [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…An incremental increase in arterial lactate reflects the failure of the Cori cycle, another signal of mitochondrial dysfunction [27-29]. In recent reports, arterial lactate was a predictor of graft dysfunction in liver transplantation, although further studies are needed to determine the best time point for lactate measurement [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Both acidosis and lactate independently predicted mortality in critically ill patients suffering from sepsis [20]. Additionally, it has been reported that lactate clearance calculated at 6 h after reperfusion of an allograft was associated with the development of early allograft dysfunction and in-hospital and 6 m mortalities after deceased donor liver transplantation [5]. In the current study, we did not evaluate the combining acidosis and hyperlactatemia and lactate clearance; therefore, fur-ther study including both of the aforementioned in a model will yield higher predictiveness of the short-term outcome in patients undergoing LT.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to those of critically ill patients, characteristics of intraoperative LA concentrations during LT have been poorly studied in a large cohort of LTs. In addition, although there are studies that found that lactate clearance shortly after reperfusion of an allograft is associated with short-term prognosis [5][6][7], research on cutoff levels of intraoperative LA to predict early mortality remains poorly investigated [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the blood lactate level is utilized to evaluate oxygen delivery to peripheral tissues in managing septic shock, alterations in lactate levels are influenced by factors other than peripheral hypoperfusion, including liver dysfunction [16,17]. Several studies reported on the benefit of lactate reduction as a clinical parameter for monitoring early graft function following liver transplantation [18][19][20]. So, far, no study has assessed the clinical application of Q-CRT in liver transplantation, although we previously evaluated Q-CRT in septic patients.…”
Section: Introductionmentioning
confidence: 99%